Molecular marker based genetic diversity assessment of Striga resistant maize inbred lines - Menkir, A.; Kling, J.; Badu-Apraku, Baffour; Ingelbrecht, I.L. (Springer, 2005)
Striga-resistant maize inbred lines are of interest to maize breeding programs in the savannas of Africa where the parasitic weed is endemic and causes severe yield losses in tropical maize. Assessment of the genetic diversity of such inbred lines is useful for their systematic and efficient use in a breeding program. Diversity analysis of 41 Striga-resistant maize inbred lines was conducted using amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers to examine the genetic relationships among these lines and to determine the level of genetic diversity that exists within and between their source populations. The two marker systems generated 262 and 101 polymorphic fragments, respectively. Genetic similarity (GS) values among all possible pairs of inbred lines varied from 0.45 to 0.95, with a mean of 0.61±0.002 for AFLPs, and from 0.21 to 0.92, with a mean of 0.48±0.003, for SSRs. The inbred lines from each source population exhibited a broad range of GS values with the two types of markers. Both AFLPs and SSRs revealed similar levels of within population genetic variation for all source populations. Cluster and principal component analysis of GS estimates with the two markers revealed clear differentiation of the Striga-resistant inbred lines into groups according to their source populations. There was clear separation between early- and late-maturing Striga-resistant inbred lines. Considering the paucity of germplasm with good levels of resistance to Striga in maize, the broad genetic diversity detected within and among source populations demonstrates the genetic potential that exists to improve maize for resistance to Striga.